The Future of Workforce Diversity: A Comprehensive Analysis of HRM Interventions for Inclusive Organizational Cultures - Kune, Debiyanti (Penelitian dan Pengembangan Ilmu, 2024)
This literature review systematically explores how Human Resource Management (HRM) interventions can be adapted to address new aspects of workforce diversity, such as neurodiversity and remote work arrangements, to foster inclusive organizational cultures. This study synthesizes key findings from existing research, focusing on the evolution of diversity management, the role of HRM interventions, and practical implications for advancing an inclusive culture. This review emphasizes the importance of organizational commitment to diversity beyond rhetoric, emphasizing the need for embedded HRM practices to leverage diversity as an asset. Additionally, this research highlights the importance of HRM policies that promote diversity and top management support in driving organizational change. These findings offer valuable insights for practitioners, diversity consultants, and academics seeking to advance diversity initiatives and build inclusive organizational cultures.